Topological solitons - Manton, Nicholas, 1952- (Cambridge monographs on mathematical physics., 2004)
This book introduces the main examples of topological solitons in classical field theories, discusses the forces between solitons, and surveys both static and dynamic multi-soliton solutions. It covers kinks in one dimension, lumps and vortices in two dimensions, monopoles and Skyrmions in three dimensions, and instantons in four dimensions.